Integrated multimodality imaging for tissue diagnostics - Joseph, James (2013)
Imaging technologies based on distinct energy sources are capable of probing complex and dynamic biological processes. Multiple imaging modalities are widely used to interrogate the subject to derive information about the complex structural and bio-molecular heterogeneities of its tissues. Although the various multi-modal imaging approaches satisfy certain clinical requirements, the level of information that can be obtained in terms of accurate registration and localisation of imaging features is constrained requiring quite long interrogation times possibly exposing to harmful ionising radiations. Further, there are no imaging schemes or very little reported works which can employ only non-ionizing radiations for multi-scale and multi-level information from the diagnosed sample. A novel multimodality system has been successfully developed that combines and integrates selected individual modalities of non-ionizing radiations such as ultrasound and optical energies together to map multi-level and multi-scale complementary information from phantom tissues. This necessitated the establishment of configuration schemes, methodologies and algorithms. Two variants of fluorescent microscopy systems were configured, investigated and compared, namely; inverted fluorescence microscope and flexible fluorescent microscope based on image fiber bundle (fluorescent microendoscope). The inverted fluorescence microscopy system was able to image at different focal planes of the sample and the lateral resolution measurements of sub-micron resolution while working with a 0.8 NA or higher NA objective lenses. The microendoscopy system configured with a gradient refractive index (GRIN) lens assembly at its distal end exhibited lateral and axial resolutions of 3.47 µm and 16 ± 0.65 μm respectively. Imaging studies performed using carboxylate-modified polystyrene microspheres coated with Nile red showed that both systems can image fluorescent features from tissue surface achieving micron or sub-micron resolutions. A proposed ultrasound imaging system having a 128 element linear array transducer supported with high end firmware and advanced post processing concepts was also developed. The system can achieve signal-to-noise ratio of 68 dB and 110 dB for single channel and whole system respectively. The in-plane and axial resolution of the system readings were 345 ±2.53 µm and 151 ± 2.24 µm respectively. Imaging studies performed on a silicone based phantom showed that the ultrasound modality system was imaging at frame rate of 68 fps from depths greater than 2.5 cm. Theoretical formulations and numerical studies to investigate the photoacoustic signal profile generated from spherical and planar geometries upon delta pulse excitation were conducted. Further, finite difference time domain (FDTD) based simulation models and related protocols for the determination of the optical properties of gold nanoparticles were formulated, modelled and verified. Selective multiple molecular targeting photoacoustic studies were demonstrated using gold nanorods with distinct aspect ratios. Further, multi-element transducer based on the photoacoustic imaging (PAI) system was established. The dual wavelength excitation of the phantom sample showed that the photoacoustic based mapping of optical absorption variations along the depth of the tissue could be performed. The imaging capabilities of the PAI system were also significantly enhanced by using spatial compounding and persistence techniques. Two novel contrast enhancement mechanisms with fluorophore–metal nanoparticle systems and a novel hybrid nanoparticle were also formulated and examined using dual- optical mode detection and imaging scheme. Correlation of the emission intensities with the photoacoustic signal amplitudes showed that the enhancements in photoacoustic signals in the fluorophore–metal nanoparticle systems were owing to the increased heat generation from fluorescence quenching. Experimental studies on the nanohybrid showed that the permanent electrostatic wrapping of two dimensional GO on Au (22 nm)-SiO2 (44nm) core-shell nanostructure enhanced the collective residual absorption of the final hybrid (GO-SiO2@AuNP) at 527 nm excitation. A novel integrated multi-modality integrated model implemented on two types of multi-modal imaging system (PAUSFI) (desktop version and flexible version) has been established. Both developed systems are able to perform and characterise near-simultaneous photoacoustic (PA), ultrasound (US) and fluorescence (FI) imaging. All the three forms of imaging modalities could map their targeted imaging features respectively. Thus, Multi-level optical and acoustic heterogeneities (complementary information) along the depth of the tissue at multi-scale resolution (<1 µm to <0.5 mm) were obtained.